Analysis of state of the art «threats» to Ukrainian startups - Kartuzov, Iegor (Technology audit and production reserves, 2021)
The object of this research is a quick recap to assess barriers on startups evolution in Ukraine after acquiring an independence 30 years ago and those developed of today. The paper aims to analyze an impact of political, historical and other factors affecting startups evolution and to understand how it decelerates an efficient functioning of technology transfer process nowadays. If one wants to establish a successful and fast-growing business, then you may need to create your own startup. The experience and practice show that it is a rather complicated process, which follows a few factors and conditions that determine its success and/or failure at the end. Being based on previously proposed efforts devoted to succinct analysis of historical, political and other premises jeopardizing transfer in Ukraine, this one is to scrutinize startups as an effective tool for such a transfer. The result of this endeavor makes a solid background for further debates in terms of political science, legal regulations and export control associated with startups and technology transfer. They highlight that startups' and DUs’ status quo implies that a global economy undergoes a number of changes related to demographic trends, technological advances, accelerated innovation and globalization. This study employs qualitative methodology and being under an umbrella of descriptive research design to accord on historical, technical, political, and other implications for startups origin as the effective mechanism for technology transfer and state’s security. This descriptive research portrays a rather accurate profile of present situation around Ukrainian startups. This design offers a profile of described relevant aspects of the problem from author's individual perspective.